Thy Children Own Their Birth: Diasporic genealogies and the descendants of Canada's Home Children - Morrison, Andrew (2006)
My research explores the cultural practices and identities of the descendants of an estimated 100,000 children who were despatched to Canada, unaccompanied by their parents, and under the auspices of a number of British charities, between 1869 and the late 1940s. It investigates the relationship between the descendants' individual and collective projects of recovery and commemoration and wider issues of postcolonial nationhood, ethnicity, and culture. It also focuses on the relationships between personal, family, national, and transnational identities, and on the ways in which the so called Home Children are being commemorated in contemporary Canada amongst competing cultural and political agendas.